Maturation and Assembly of Iron-Sulfur Cluster-Containing Subunits in the Mitochondrial Complex I From Plants - López-López, Alicia; Keech, Olivier; Rouhier, Nicolas (Frontiers in Plant Science, 2022)
In plants, the mitochondrial complex I is the protein complex encompassing the largest number of iron-sulfur (Fe-S) clusters. The whole, membrane-embedded, holo-complex is assembled stepwise from assembly intermediates. The Q and N modules are combined to form a peripheral arm in the matrix, whereas the so-called membrane arm is formed after merging a carbonic anhydrase module with so-called Pp (proximal) and the Pd (distal) domains. A ferredoxin bridge connects both arms. The eight Fe-S clusters present in the peripheral arm for electron transfer reactions are synthesized via a dedicated protein machinery referred to as the iron-sulfur cluster (ISC) machinery. The de novo assembly occurs on ISCU scaffold proteins from iron, sulfur and electron delivery proteins. In a second step, the preformed Fe-S clusters are transferred, eventually converted and inserted in recipient apo-proteins. Diverse molecular actors, including a chaperone-cochaperone system, assembly factors among which proteins with LYR motifs, and Fe-S cluster carrier/transfer proteins, have been identified as contributors to the second step. This mini-review highlights the recent progresses in our understanding of how specificity is achieved during the delivery of preformed Fe-S clusters to complex I subunits.